PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, OPINI AUDIT TAHUN SEBELUMNYA, DAN LIKUIDITAS TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN TAMBANG DAN AGRICULTURE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Yulianto, Yulianto; Tutuko, Bambang; Larasati, Meita (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThis study aims to determine how the influence of company size, profitability, previous year's audit opinion, and liquidity on going concern audit opinions in mining and agriculture sector companies that have been listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period.The population of this research is mining and agriculture sector companies that have been listed on the Indonesia Stock Exchange (IDX). The sample selection technique used was purposive sampling and obtained 7 (seven) companies. The data collection technique used in this study is secondary data, namely tracing the financial statements of mining and agriculture sector companies for 2014-2018 through the IDX website (www.idx.co.id).The results showed that partially company size had no effect on going concern audit opinion with a significance level of 0.457> 0.05. Profitability variable partially affects going-concern audit opinion with a significance level of 0.031> 0.05. The audit opinion variable in the previous year partially influences going-concern audit opinion with a significance level of 0.010> 0.05. The liquidity variable partially has no effect on going concern audit opinion with a significance level of 0.722> 0.05. The effect of company size, profitability, previous year's audit opinion, and liquidity simultaneously affects going-concern audit opinion with a significance level of 0.000 <0.05.